Penerapan Media Spining Wheel Flashcard Untuk Meningkatkan Pengenalan Kosakata Pada Materi Bermain Dan Bergerak Kelas 1 Di Sekolah Dasar - Nurhalizah, Marsyanda; Irmaningrum, Rizka Novi; Khasanah, Linaria Arofatul Ilmi Uswatun (Jurnal Kiprah Pendidikan, 2025)
The use of media in teaching is a part that must receive attention from teachers as facilitators in every learning activity. Teachers will get various kinds of convenience in teaching if they are able to use learning media as a teaching aid, as well as overcome the problem of student boredom in the teaching and learning process. This type of research is classroom action research (CAR). This research uses two cycles, namely cycle I and cycle II which consist of planning, implementation, observation and reflection. The subjects of this research are all class I of SDN 2 Sukomulyo Lamongan. The data collection techniques used are tests (pretest and posttest), observation and documentation. The results of this study can be concluded that: (1) Observation of teacher activities in cycle I obtained an average of 51% and cycle II was 88.30%. From cycle I and cycle II there was an increase of 65.29%. (2) Observation of student activities in cycle I obtained an average of 51% and cycle II was 89%. From cycle I and cycle II there was an increase of 53.98%. (3) Student learning outcomes in cycle I achieved an average of 40% and cycle II 80%. From cycle I and cycle II, student learning outcomes experienced an increase of 40%. The conclusion is that the use of media improves student learning outcomes in vocabulary recognition for playing and moving material for class I SDN 2 Sukomulyo..